Belief and practice as illustrated by John XXII’s excommunication of Robert Bruce - Hill, Rosalind M. T. (Studies in church history, 1972)
The sentence of excommunication was the ultimate spiritual deterrent available to the medieval Church. It was designed to be completely terrifying, and to the devout mind it probably was. In theory, it cut the offender off not only from his hope of eternal salvation but, as many a person found to his cost, from all contacts which made mortal life bearable, or indeed possible. But theory, as father Logan has shown us, is not the same thing as practice. The effectiveness of the sentence was limited both by the character of the person afflicted and, to some extent, by his social position. A king could get away with a good deal, and, for lesser men, the existence of the writ de excommunicato capiendo tacitly acknowledged the fact that a royal prison might be a more effective inducement to repentance than the terrors of the Church’s ban. To some extent the Church itself had asked for trouble by cheapening the sentence. Many a modern librarian must wish for a suitably unpleasant punishment for those who borrow books and fail to return them, but when we find a bishop of Lincoln ordering the excommunication, after trina monitio, of all those who have failed to return a book borrowed from Master John of Dersingham, we may wonder whether a sledgehammer were not being used to crack a nut.John XXII’s excommunication, in 1318, of Robert Bruce certainly does not fall into the category of excommunication for trivial causes, whatever one may think of the rights of the case, but the way in which the pope attempted, and Bruce frustrated, the execution of the sentence provides an interesting example of the difference between theory and practice in matters of ecclesiastical administration. The pope started from the assumption that Bruce was a lawful and distinguished subject of the king of England who had regrettably defected from his allegiance.